General practitioner use of D-dimer in suspected venous thromboembolism: historical cohort study in one geographical region in the Netherlands. Issue 5 (28th May 2019) - Schols, Angel M R; Meijs, Eline; Dinant, Geert-Jan; Stoffers, Henri E J H; Krekels, Mariëlle M E; Cals, Jochen W L
Abstract : Objectives: To investigate how many general practitioner (GP)-referred venous thromboembolic events (VTEs) are diagnosed during 1 year in one geographical region and to investigate the (urgent) referral pathway of VTE diagnoses, including the role of laboratory D-dimer testing. Design: Historical cohort study. Setting: GP patients of 47 general practices in a demarcated geographical region of 161 503 inhabitants in the Netherlands. Participants: We analysed all 895 primary care patients in whom either the GP determined a D-dimer value or who had a diagnostic work-up for suspected VTE in a non-academic hospital during 2015. Primary and secondary outcome measures: The primary outcomes of this study were the total number of VTEs per year and the diagnostic pathways—including the role of GP determined D-dimer testing—of patients urgently referred to secondary care for suspected VTE. Additionally, we explored the use of an age-adjusted D-dimer cut-off. Results: The annual VTE incidence was 0.9 per 1000 inhabitants. GPs annually ordered 5.1 D-dimer tests per 1000 inhabitants. Of 470 urgently GP-referred patients, 31.3% had a VTE. Of those urgently referred based on clinical assessment only (without D-dimer testing), 73.8% (96/130) had a VTE; based on clinical assessment and laboratory D-dimer testing yielded 15.0% (51/340) VTE. Applying age-adjusted D-dimer cut-offs to all patients aged 50 years or older resulted in a reduction of positive D-dimer results from 97.9% to 79.4%, without missing any VTE. Conclusions: Although D-dimer testing contributes to the diagnostic work-up of VTE, GPs have a high detection rate for VTE in patients who they urgently refer to secondary care based on clinical assessment only.